Molecular Characterization and Genotype-Phenotype Correlation of G6PD Mutations in Five Ethnicities of Northern Vietnam - Thi Thao Ngo; Thinh Huy Tran; Thanh Dat Ta; Thi Phuong Le; Phuoc Dung Nguyen; Mai Anh Tran; The-Hung Bui; Thanh Van Ta; Van Khanh Tran (Anemia)
Glucose-6-phosphate dehydrogenase (G6PD) deficiency is the most common enzyme disorder and is caused by G6PD gene mutations. To date, more than 400 variants in the G6PD gene have been discovered, and about 160 identified variants are associated with a significant decrease in the G6PD enzyme activity. However, the molecular characterization and epidemiological study of G6PD deficiency are still limited in Vietnam. Therefore, we conducted this study to determine the G6PD variants among the Vietnamese populations and evaluate their correlation to G6PD enzyme activity. A total of 339 patients (302 males and 37 females) were enrolled in this study. The G6PD variants were identified by Sanger sequencing. Our results indicate that males are more severely deficient in G6PD than females. This enzyme activity in males (1.27 ± 1.06 IU/g·Hb) is significantly lower than in females (2.98 ± 1.57 IU/g·Hb) (p<0.0001). The enzyme activity of the heterozygous-homozygous females and heterozygous females-hemizygous males was found to be significantly different (p<0.05), which is interpreted due to random X-inactivation. For G6PD molecular characteristics, Viangchan (c.871G>A), Canton (c.1376G>T) and Kaiping (c.1388G>A) variants were the most dominant, accounting for 24.48%, 17.70%, and 22.42%, respectively, whereas the highest frequency of complex variants was observed in Viangchan/Silent with 20.35%. In terms of G6PD activity, the Union variant presented the lowest mean value (1.03 IU/g·Hb) compared to the other variants (p<0.05). Computational analysis using Polyphen-2 tool investigated that all variants were relative to G6PD deficiency and separated the levels as benign and damaged. The result will establish effective methods to screen G6PD variants in Vietnam.